Dorongan Masyarakat Jawa Timur Menjadi Pekerja Migran Indonesia - Maulidyah Amalina Rizqi (Jurnal Manajerial, 2023)
Background - The unemployment rate in East Java province is below the national average and the poverty rate in East Java province has decreased from the previous year. However, the number of Indonesian migrant workers originating from East Java ranks first nationally. Objectives - The aim of this research is to prove that there is a drive from within the community to become migrant workers. Researchers also want to find out what things make the people of East Java to become migrant workers. Design/ Methodology/ Approach - This study uses a Descriptive-Qualitative paradigm approach, with data collection techniques in the form of interviews with active and non-active Indonesian migrant workers (ex immigrants). Findings - Some of the elements that encourage people to become Indonesian immigrant workers are invitations from family, colleagues or friends, low income, economic improvement, living facilities and low education. Some of these elements are the encouragement or motivation of individuals to meet several needs in personal and social life and each individual wants to fulfill these needs in his life. Conclusion - This research produced several elements that encouraged the people of East Java, especially to become Indonesian immigrant workers, namely invitations from family, colleagues or friends, low income in Indonesia, economic improvement, living facilities and low education. Some of these elements are the encouragement or motivation of individuals to fulfill several needs in personal and social life. Research Implications - This research has important implications for the general public, Indonesian immigrant workers as well as for future research. The general public will know what things might happen when they become immigrant workers, and how the immigrants survive in other countries in order to improve their family's economic standard. Immigrant workers can meet their needs in life, while further researchers can dig deeper into other elements that encourage immigrant workers to work abroad. Research Limitations - This research was conducted only in certain areas. The northern region is represented by the northern coastal area of ​​Lamongan, the southern region is represented by Trenggalek Regency, the western region is represented by Ngawi Regency, and finally the eastern region is represented by Sumenep Regency and prioritizes the small island in Sumenep, namely Sapudi Island.